Risk Management Excellence in the Live Streaming Agency - Yoana Anggreini; Edi Hamdi; Dimas Angga Negoro; Muhammad Dhafi Iskandar (Manunggal Halim Jaya, 2026)
This activity aims to identify potential risks faced by PT COT, analyze the probability and impact levels of risks, and evaluate the implementation of a risk management framework based on the principles of ISO 31000:2018. The activity method uses a qualitative descriptive approach, with case studies, interviews, observations, and documentation. The results of the activity indicate that PT COT faces risks across operational, financial, technological, legal, and human resource areas. Short-term risk management objectives focus on policy formulation, socialization of the framework, and the implementation of initial risk assessments. Medium-term objectives focus on strengthening information security, implementing a cybersecurity early-detection system, and preparing a Business Continuity Plan (BCP) and a Disaster Recovery Plan (DRP). Meanwhile, long-term objectives emphasize regulatory and technology evaluation, partner dependency risk mapping, and business portfolio diversification. This activity concludes that PT COT has designed a systematic, integrated, and continuous-improvement-oriented risk management system, thereby minimizing potential losses while supporting the company's resilience and competitiveness in the e-commerce live-streaming industry.